Irrigation and energy: issues and challenges - Belaud, G.; Mateos, L.; Aliod, R.; Buisson, Marie-Charlotte; Faci, E.; Gendre, S.; Ghinassi, G.; Gonzales Perea, R.; Lejars, C.; Maruejols, F.; Zapata, N. (Wiley, 2020)
Water-efficient agriculture has implied a large increase in energy consumption for irrigation in recent decades. In many irrigation systems, energy costs are now threatening their sustainability. However, new opportunities have arisen for the use of renewable energies in the irrigation sector. These are some of the aspects of the multifaceted multiple-actor ‘water–food–energy’ nexus. Technical, economic and environmental issues are linked in many ways, involving farmers, water users’ associations, energy suppliers, engineers and other stakeholders. The ICID session ‘Irrigation and energy’ triggered discussions on these multiple dimensions. This paper presents a synthesis of the presentations, discussions and conclusions. Four main questions are addressed: How do irrigation productivity and sustainability of water resources exploitation change when farmers have access to energy? What do we know about energy efficiency in irrigation systems, at farm and collective network levels? How can this efficiency be optimized by using advanced technologies, modelling tools, improved management? Is energy production an opportunity for irrigation systems? These questions have been posed based on multiple case studies from different parts of the world. The BRL network, in southern France, illustrates advanced strategies and opportunities to reduce energy consumption and develop energy production at a network level. General conclusions are drawn from this synthesis, illustrating trade-offs and synergies that can be identified in the irrigation sector at different scales, while opportunities for future research are proposed.